Student and teaching characteristics related to ratings of instruction in medical sciences graduate programs. - Donnon T; Delver H; Beran T (Medical Teacher, 2010)
Background: Although the validity of students' ratings of instruction has been documented, several student and course characteristics may be related to the ratings students give their instructors. Aims: The purpose of this study was to examine student ratings obtained from the Universal Student Ratings of Instruction (USRI) instrument. These responses were compared to various student characteristics. Also, teaching characteristics that were most closely associated with the ratings were determined. Method: A total of 1738 USRI forms were completed by graduate students enrolled in medical science courses from 1999 to 2006 in the Faculty of Medicine at a Canadian university. Results: Between group comparisons showed that negative student perceptions about the course (i.e., did not have the freedom to select), perceiving the course workload as high, and low grade expectations held were related to negative student ratings of overall quality of instruction. In terms of the student and teaching characteristics, organization of course material and perceptions of whether students felt they learned a lot in the course were most closely related to global ratings of instructional quality. Conclusion: Implications for teaching focus on improving the organization and delivery of course content that meets the learning objectives of graduate students in medical sciences.